Peran Strategis Belanja Perjalanan Dinas dalam Mendorong Perekonomian Sektor Pariwisata: Analisis Data Panel di Indonesia - Priambodo, Aln Pujo; Yuniarianti, Alfiana (Jurnal Manajemen Perbendaharaan, 2025)
Indonesia's tourism sector holds substantial potential for driving community-level economic development. Within this sector, the accommodation and food and beverage services are among the primary beneficiaries of government travel expenditures. Nevertheless, such expenditures are often perceived merely as operational or supporting activities with limited macroeconomic implications. Therefore, this study aims to examine the effect of government travel spending on the economy, particularly in the tourism sector. The impact is measured by using the best panel regression model among Fixed Effect, Random Effect, Pooled OLS, First Difference, Between OLS, and Fama-MacBeth models. The Between OLS estimation emerged as the best-fitting model, revealing that government travel spending significantly contributes to tourism sector growth, with an estimated increase of 0.64 points for each additional spending. Additionally, other independent variables—such as the human development index, foreign direct investment, and domestic direct investment—also positively contribute to the RGDP in the accommodation and food and beverage sector.